The influence of coal mining subsidence on the movement and deformation of loess slope in the loess gully area of Northern Shaanxi - Zheng, Beibei; Song, Shijie; Cheng, Xia; Niu, Ruilin; Cheng, Xing; Ruan, Hao; Li, Guodong (Frontiers in Earth Science, 2023)
Introduction: How to solve the contradiction between coal mining and soil and water conservation is a key scientific problem to realize ecological environment protection and high-quality development in the middle reaches of the Yellow River. Methods: Using FLAC3D numerical simulation experiment method, the influence of loess slope surface shape and coal seam overburden structure coupling on slope movement and deformation is studied. Results: Under any surface slope shape, the average slope subsidence coefficient (q slope average) increases with the increase of sand layer coefficient after coal mining subsidence. When the sand layer coefficient is less than 0.71, the q slope average increases rapidly, with an increase of more than 2.86%, and when the sand layer coefficient is greater than 0.71, the q slope average tends to be stable. Under any surface slope shape, the q slope average decreases with the increase of sand-mud ratio. When the overburden structure characteristics of any coal seam and the natural slope of the surface slope are less than or equal to 5°, the q slope average of the convex slope is the largest, and the q slope average of the four slope types is ranked as follows: convex slope > straight slope ≈ composite slope > concave slope; When the structural characteristics of overlying strata in any coal seam and the natural slope of surface slope are more than 5°, the q slope average of concave slope is the largest, and the q slope average of four slope types is in the order of concave slope > straight slope ≈ composite slope > convex slope. With the increase of the natural slope of the surface slope, the q slope average first decreases and then increases, and the inflection point is 15°. The influence law of loess slope surface morphology and coal seam overburden structure on the average horizontal movement of slope surface is similar to that of average subsidence of slope surface. Discussion: The results can provide scientific basis for surface movement and deformation and soil and water conservation in the mining subsidence area of northern Shaanxi in the middle reaches of the Yellow River Basin in China.